KONSEP UQBAH MADRASIYYAH PERSPEKTIF M. ATHIYYAH AL-ABRASYI DAN RELEVANSINYA DALAM PENDIDIKAN ISLAM KONTEMPORER - Alfitri Alfitri; Maragustam Siregar (Jurnal Eduslamic, 2026)
The imposition of sanctions on students is an integral part of the educational system, as not all students are able to maintain discipline and avoid violating the established norms. However, in practice, there are numerous cases of violations that harm students, particularly in the form of physical violence, which can lead to psychological trauma and even physical injury. On the other hand, when such cases become widespread, educators are faced with a moral dilemma: whether to allow students' indiscipline to persist or to impose sanctions for the violations they have committed. In such situations, a solution is needed so that both parties can receive their rights in a proportional manner. One proposed solution is the implementation of the concept of Uqubah Madrasiyyah (school sanctions) as explained by M. Athiyyah al-Abrasyi. This study is a literature review focusing on M. Athiyyah’s ideas in the field of Islamic education, particularly regarding the imposition of school sanctions on students. The results of this study indicate that M. Athiyyah al-Abrasyi’s thoughts on this matter are based on three key aspects: purpose, principles, and the technical application of sanctions on students. These three aspects are highly relevant to the implementation of contemporary Islamic education, ensuring that students are protected while educators retain the right to administer sanctions appropriately.